MicroRNA-210 Protects PC-12 Cells Against Hypoxia-Induced Injury by Targeting BNIP3 - Luan, Yonggang; Zhang, Xiaoli; Zhang, Yongli; Dong, Yubin (Frontiers in Cellular Neuroscience, 2017)
MicroRNA (miR)-210 is the most consistently and predominantly up-regulated miR in response to hypoxia in multiple cancer cells. The roles of miR-210 in rat adrenal gland pheochromocytoma (PC-12) cells remain unknown. We aimed to explore the possible effect of miR-210 in neonatal brain injury. We explored the potential molecular mechanism by using PC-12 cells under hypoxia. Scramble miRs, miR-210 mimic, miR-210 inhibitor or its negative control were respectively transfected into PC-12 cells. Cell viability, migration, invasion and apoptosis were also assessed to evaluate hypoxia-induced cell injury. The expression level of miR-210 was identified by quantitative real-time PCR analysis. Apoptosis-related protein expression as well as key kinases in the PI3K/AKT/mTOR signal pathway was studied by Western blot analysis. Hypoxia suppressed cell viability, migration and invasion, but promoted apoptosis through activation of mitochondrial- and caspase-dependent pathways. Hypoxia markedly induced up-regulation of miR-210 in PC-12 cells. Overexpression of miR-210 protected PC-12 cells against hypoxia-induced injury. Bcl-2 adenovirus E1B 19 kDa-interacting protein 3 (BNIP3) was proven to be a target gene of miR-210 in PC-12 cells. miR-210 overexpression ameliorated the hypoxia-induced injury in PC-12 cells by down-regulating BNIP3. Hypoxia-induced alterations of key kinases in the PI3K/AKT/mTOR signal pathway were affected by aberrant expression of BNIP3. These findings suggested that miR-210 protected PC-12 cells against hypoxia-induced injury by targeting BNIP3, involving the PI3K/AKT/mTOR signal pathway.